2008
DOI: 10.3323/jcorr.57.536
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Stainless Steel in Nitric Acid Solutions Including Neptunium

Abstract: In order to investigate a corrosion behavior of stainless steel in the typical nuclear fuel reprocessing plant, corrosion tests using nitric acid solution with neptunium were conducted under atmospheric and the reduced pressure conditions in the laboratory where radioactive substance could be handled. An ultra low carbon type of SUS304ULC stainless steel was used. Obtained results were as follows: Under the reduced pressure condition, corrosion of the stainless steel was accelerated in the nitric acid solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Among these chemicals, Pu and Np are radioactive and included in spent nuclear fuels. We have already reported that small amount of Np addition in the nitric acid solution accelerated corrosion rate dominantly (7). We suggested that Np was probably reoxidized in the boiling nitric acid solution but the actual evidence was not obtained because of difficulties of handling Np.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among these chemicals, Pu and Np are radioactive and included in spent nuclear fuels. We have already reported that small amount of Np addition in the nitric acid solution accelerated corrosion rate dominantly (7). We suggested that Np was probably reoxidized in the boiling nitric acid solution but the actual evidence was not obtained because of difficulties of handling Np.…”
Section: Introductionmentioning
confidence: 94%
“…For example, Kajimura showed improved material reduced C, P and S content from austenitic stainless steel (6). And also, Cr, Ce, Ru Pu and Np were reported for the chemical species accelerated corrosion (3,5,(7)(8)(9). Among these chemicals, Pu and Np are radioactive and included in spent nuclear fuels.…”
Section: Introductionmentioning
confidence: 99%
“…A promising 3D characterization approach has also been attempted by µ-Xray-tomography [34]. The measurement of the mass loss as the function of time gives also important information regarding the kinetics of IGC [18,24,26,[29][30][31][35][36][37][38][39][40][41]. Sometimes, the chemical characteristics of the surface are analyzed by X-ray photoelectron spectroscopy (XPS) [26,38,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that IGC could be dependent on the surface exposed to corrosive medium regarding the rolling direction [29,30,39,49], on the chemical composition of the SSs, which in turn influence the chemical composition of the grain boundaries [15,18,24,25,30,38,42,43,50,51], on the grain size [40] and on the metallurgical treatment [35]. IGC of SSs was also studied in a pure nitric medium at different concentrations [38,42] but also with the addition of different oxidizing species at different levels [36,37,49,51]. However, these parameters were only correlated to the corrosion potential and corrosion kinetics, without further information about the material/solution interface in terms of chemical composition and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…7 SEM photographs of corroded sample surfaces in boiling HNO 3 solution with and without Np addition. 24) 3.3 Np の代替金属イオンを用いた腐食現象の再現試験 Fig.9 10 にそれぞれ示す Fig.9 (a) に示した全 Cr 量 は 時間に伴って増加している これはステンレス鋼の 腐食に伴って溶出した Cr が溶液中に蓄積したためであ る (b) に示した Cr 6+ 量は時間経過に伴い減少していく その傾向は硝酸濃度が高いほど大きく ステンレス鋼の 腐食速度と対応がある すなわち Cr 6+ はステンレス鋼の 腐食の対反応として還元され Cr 3+ になったと考えられる これに対して Fig.10 (b…”
unclassified